Does Visiting Art Museums Improve Psychological Well-being? A Quantitative Study in Pasifika Museum - Aryasih, Putu Ayu; Puja, Ida Bagus Putu; Rahman, Maulana; Sangka, Sitri Setya (Journal of Mandalika Review, 2025)
Introduction: While art museums are ubiquitous cultural institutions, their role in enhancing psychological well-being remains underexplored. This study addresses this gap by investigating how art museum visits influence multidimensional psychological well-being, offering novel insights into their societal purpose beyond education and tourism. Methodology: A survey was conducted with 40 visitors at Bali’s Pasifika Museum, utilizing an adapted version of Ryff’s (1989) Psychological Well-Being Scale (α = 0.889). Descriptive statistical analysis was applied to assess six well-being dimensions: autonomy, environmental mastery, personal growth, positive relationships, purpose in life, and self-acceptance. The sampling technique used in this research is incidental sampling technique. Findings: Results revealed significant improvements in psychological well-being, with an average score of 102.75 (range: 70–126), Personal growth and positive relationships emerged as the most impacted dimensions, highlighting art museums’ capacity to foster self-discovery and social connection. Conclusion: This study demonstrates that art museums function not merely as repositories of culture but as accessible spaces for mental and emotional flourishing. Practically, the findings advocate for museums to design exhibits prioritizing interactive engagement and cross-cultural narratives, positioning museums as wellness destinations. However, the study’s limitations include the modest sample size, non-representative incidental sampling, and single-site focus restricting generalizability across cultural contexts.